Fire in the star : the unicorn quest 3 - Benko, Kamilla (London : Bloomsbury Children's Books, 2020)
"When Claire discovers that 'only a queen can defeat a queen,' she knows she must steal and reforge the ancient Crown of Arden to stand a chance against the darkness that threatens the world and her family"
Keywords: Children's stories; Fantasy fiction; Adventure and adventurers Fiction